Review of Parameters in Routing Protocols in Vehicular Ad-hoc Networks - Intisar Mohsin Saadoon; Maha Ali Hussein; Farah Neamah Abbas (Newinera Publisher, 2022)
Vehicular Ad_hoc Network (VANET) is a sophisticated elegance of devoted cellular network that permits automobiles to intelligently communicate for different roadside infrastructure. VANETs bring with it some of demanding situations associated with Quality of Service (QoS) and performance. QoS relies upon on many parameters which includes packet transport ratio, bandwidth, postpone variance, records latency, etc. This paper, discuss numerous troubles associated with latency records, bandwidth usage, and transport of packet in VANETs. The demanding situations have been recognized in offering security, reliability and confidentiality of posted records. Finally, numerous packages of VANETs also are introduced in the modern computing scenario.